Exploring Network Security Educator Knowledge - Jennifer B. Chauvot; Deniz Gurkan; Cathy Horn (Journal of Cybersecurity Education, Research & Practice)
It is critical for nations to have trained professionals in network security who can safeguard hardware, information systems, and electronic data. Network security education is a key knowledge unit of the National Centers of Academic Excellence in Cybersecurity and various information systems security curricula at the master's and bachelor's levels in higher education. Network security units are components of computer science curricula in high school contexts as well. Educators who teach these concepts play a significant role in developing a skilled workforce of network security experts for both governmental and non-governmental organizations. Understanding the necessary knowledge and skills of network security educators serve to better inform institutes of higher education, educator preparation programs, and others who support educators in the field. This study describes knowledge constructs of a higher education faculty member who teaches networking and network security and was developing, and piloting innovative network security curriculum embedded in both undergraduate and graduate courses. Data were transcripts of recorded monthly meetings with the educator, fieldnotes taken during the meetings, and course artifacts. Existing teacher knowledge frameworks that have been applied in both K-12 and higher education contexts were used to deductively code the data. Examples of curricular knowledge and pedagogical content knowledge specific to the teaching of network security are provided. The affordances of using engagement within curriculum development to understand educator knowledge constructs and the existing teacher knowledge frameworks as tools for analyses are highlighted.